EFFECT OF ARTHROSPIRA PLATENSIS AS A FOOD SUPPLEMENT AGAINST SODIUM FLUORIDEINDUCED INTOXICATION ON SOFT TISSUES OF MALE WISTAR ALBINO RATS - Kandula, Ravindra Reddy; Korlakunta, Narasimha Jayaveera; Mitta, Raghavendra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of the present study was to explore the in vitro antioxidant and effect of hydroalcoholic extract of Arthrospira platensis (ASP) against sodium fluoride (NaF)-induced toxic effects on soft tissues (heart, liver, and kidney). Methods: In vitro antioxidant activity was assessed using 1,1-diphenyl-2-picrylhydrazyl radical scavenging, 2,2'-azino-bis(3-ethylbenzothiazoline- 6-sulphonic acid) radical scavenging, metal chelation, total antioxidant and reducing power assays, and total flavonoid and phenol content. In this study, 36 male Wistar albino rats were divided into six groups of six animals each. Animals were served as Group I - normal control, Group II - toxic control, and Groups III, IV, and V - treatment groups, which received hydroalcoholic extract of ASP at doses of 100, 200, and 400 mg/kg body weight (p.o), respectively. Group VI served as plant control received hydroalcoholic extract of ASP at a dose of 400 mg/kg body weight (p.o). All groups except Groups I and VI received NaF (100 ppm) through drinking water for 30 days. Results: Results showed that intoxication of NaF caused significant elevation of serum biomarkers of the heart, liver, and kidney and altered tissue oxidative stress markers' levels. Administration of hydroalcoholic extract of ASP significantly normalized elevated serum levels of heart (p<0.001), liver (p<0.001, p<0.05), and kidney biomarkers (p<0.001). Decrease in lipid peroxidation and increase in reduced glutathione and catalase enzyme levels in a dose-dependent manner were observed in soft tissues (p<0.001, p<0.01, and p<0.05). Conclusion: The study revealed that ASP has good antioxidant and mitigative action against NaF intoxication on soft tissues.